Efficient Spectrum Sharing by Cognitive User Section Through Clustering for D2D Communication - et. al., T.Balachander , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: D2D communication is the direct communication between the wireless network node without the base station's involvement. This direct communication requires spectrum to communicate, which can be leveraged by using a cognitive radio approach through spectrum sharing. Spectrum sharing using sensed free channel among N number of cognitive users is one of the research issues and is an NP-hard problem. This spectrum sharing also called cognitive user selection. Channel sate-based user selection is usually carried. This user selection is carried out in such a way the sum rate in the network will be maximized. Here in this paper, a graph theory-based approach is followed. The entire node-set, which will share the spectrum, is represented as a weighted graph. The interference between the node that shares the spectrum is represented as the edge of the graph, and the participating cognitive user is represented as a node of the graph. Then clustering mechanism is applied to group the node as an interference-free set, and the cognitive user nodes are selected for the share the spectrum. The proposed mechanism simulation result proves that the mechanism can achieve a maximum sum rate.